Have RCTs brought back the "Empirical" into Economics?. (March 2020) - Surendran, Aardra; Kumar, Awanish
Abstract: The experimental turn in economics has garnered numerous responses from its supporters and critics alike. One of the under-examined claims made by the Randomistas is that their approach has brought back the empirical into Economics. We counter this position at two levels. At a preliminary level, this is a mis-characterisation of research within economics. At a more fundamental level, the experimental approach represents a confused conception of the relationship between theory and empirics, rendering theory as a purely cognitive activity of which RCTs are the empirical form. Our critique draws from the realist view of social science research in which the empirical and the theoretical are interspersed into each other.